2004
DOI: 10.1152/ajplung.00126.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of serum potentiation of GM-CSF production by human airway smooth muscle cells

Abstract: Inflammation and vascular leakage are prevalent in asthma. This study aimed to elucidate the mechanisms involved in serum potentiation of cytokine-induced granulocyte macrophage colony stimulating factor (GM-CSF) production by human airway smooth muscle cells and to identify possible factors responsible. Serum-deprived cells at low density were stimulated with TNF-α and IL-1β for 24 h. Human AB serum (10%), inhibitors of RNA and protein synthesis or specific signaling molecules, or known smooth muscle mitogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Recent evidence using newly developed pharmacological inhibitors identified the necessary NF-B-activating kinase, IKK␤, as a potential new target for treatment of inflammatory responses in asthma (Birrell et al, 2005). We and others showed that NF-B is activated by TNF␣ or IL-1␤ in ASM cells and represents an essential transcription factor involved in the regulation of VCAM-1 (Issa et al, 2006), ICAM-1 (Amrani et al, 1999), CXC chemokine growth-related oncogene protein-␣ (Issa et al, 2006), and granulocyte macrophage-colony-stimulating factor (Lalor et al, 2004). Through the use of BMS-345541, a potent IKK␤ inhibitor (Burke et al, 2003), we demonstrated here that NF-B also played a central role in IFN␥-sensitive, TNF␣-inducible genes IL-6, IL-8, and eotaxin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence using newly developed pharmacological inhibitors identified the necessary NF-B-activating kinase, IKK␤, as a potential new target for treatment of inflammatory responses in asthma (Birrell et al, 2005). We and others showed that NF-B is activated by TNF␣ or IL-1␤ in ASM cells and represents an essential transcription factor involved in the regulation of VCAM-1 (Issa et al, 2006), ICAM-1 (Amrani et al, 1999), CXC chemokine growth-related oncogene protein-␣ (Issa et al, 2006), and granulocyte macrophage-colony-stimulating factor (Lalor et al, 2004). Through the use of BMS-345541, a potent IKK␤ inhibitor (Burke et al, 2003), we demonstrated here that NF-B also played a central role in IFN␥-sensitive, TNF␣-inducible genes IL-6, IL-8, and eotaxin.…”
Section: Discussionmentioning
confidence: 99%
“…Total cell lysates were prepared (19) and subjected to SDS-PAGE gel electrophoresis and Western blotting. The Iκ-Bα and phosphorylated p65 bands were detected using Phospho-NF-κB p65 (Ser276) and Iκ-Bα antibodies diluted 1/1,000 and 1/500, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Growth-arrested ASM cells were treated with PD98059 (30 μM), SB203580 (10 μM), SP600125 (10 μM), or the negative control SB202474 (10 μM), as previously reported (19, 29). The cells were treated with the inhibitors or their vehicle (0.1% vol/vol DMSO) 45 min before and during stimulation with the cytokines for 24 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ASMCs in six-well plates were treated with agents or vehicle as described above and stimulated with cytomix for 2.5, 5, 10, and 30 min. Whole cell lysates were prepared as previously described (30). Each sample (25 l) was subjected to SDS-PAGE and Western blot analysis.…”
Section: Reagentsmentioning
confidence: 99%